Kajian kenderaan mini serbaguna berkuasa elektrik untuk Industri Pelancongan : Kajian kes di Bandaraya Kuching, Sarawak - Kueh, Perng Yaw (Universiti Malaysia Sarawak (UNIMAS), 2007)
The purpose of the study is to identify the problem among local public transport and to propose a Mini Multi-Purpose Electric Vehicle for tourist. The design will offer new image of public transport in Kuching and provide better quality services. This vehicle is powered by electric engine and caters for seven passengers in one time. The whole design is emphasis on ergonomic factor such as safety and comfort elements. The concept of this design is urban, sleek and practical.